Chemical Quality Analysis and Antibacterial Properties of Eco-enzyme Derivative Products as Liquid Organic Fertilizers and Natural Disinfectants - Najla Lubis; Rizki Damayanti; Sheila Wardani (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2025)
Bioz Nutrition is the product of second-stage fermentation of eco-enzyme (EE) or Garbage Enzyme (GE) for 21 days with the addition of specific organic materials. This study aimed to evaluate the potential of Bioz in enhancing plant nutrient content and exhibiting antibacterial activity as a natural disinfectant. Two types of Bioz, coded Bioz1-n and Bioz2-n, were produced through a process involving four main stages: the production of EE from pineapple and orange waste via anaerobic fermentation for 100 days; the production of Bioz through further fermentation of EE for 21 days with added organic materials; analysis of the chemical composition (nitrogen, phosphorus, potassium, and pH) and evaluation of antibacterial and antifungal activities; and testing against S. aureus (Gram-positive) and E. coli (Gram-negative) using the disc diffusion method. Chemical analyses were conducted using the Kjeldahl method (N), UV-Vis spectrophotometry (P and organic carbon), atomic absorption spectrophotometry (K), and a pH meter. Antibacterial and antifungal activities were tested at various dilution ratios of EE to water (1:0, 1:10, 1:50, and 1:100). The results showed that second-stage fermentation improved the nutritional content of Bioz and that a 1:10 dilution (Bioz1-1 and Bioz2-1) was the most effective in inhibiting bacterial growth, indicating its potential as a natural disinfectant. This process provides a sustainable approach to utilizing agricultural waste, adding economic value while supporting environmentally friendly agricultural and household applications.